2018
DOI: 10.24874/jsscm.2018.12.02.06
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Analysis of Fatigue Behavior of a Fully Composite-Based Designed Hip Resurfacing Prosthesis

Abstract: The Hip resurfacing prosthesis is subjected to different stresses resulting from the different positions of the human walk, thereby generating dynamic stresses that vary with time, leading the implant material to fatigue failure. It is important to study the fatigue behavior of the prosthesis material and to ensure its long lifetime. We proposed a new composite material named CF/PA12 composed of carbon fibers with a polyamide 12 resin, whose biocompatibility had been demonstrated in laboratories. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…The findings obtained indicated that hip resurfacing prosthesis fully made of carbon fiber polyamide 12 composite sustain the applied loads. The maximum stresses obtained were low than the yield stress, indicating that hip resurfacing prosthesis designed using carbon fiber polyamide 12 composite material was safe against failure [45].…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…The findings obtained indicated that hip resurfacing prosthesis fully made of carbon fiber polyamide 12 composite sustain the applied loads. The maximum stresses obtained were low than the yield stress, indicating that hip resurfacing prosthesis designed using carbon fiber polyamide 12 composite material was safe against failure [45].…”
Section: Introductionmentioning
confidence: 87%
“…Molded hip implants have also been used to carry out mechanical performance testing of carbon fiber polyamide 12. There have been limited studies that use the finite element method to predict the degree of accuracy of 3D printed carbon fiber polyamide 12 hip implant surfaces [43–47]. However, the use of the finite element method to assess the effect of 3D printing process parameters on the properties of 3D printed implant is hypothesized to enhance dimensional control and surface finish of joint components.…”
Section: Introductionmentioning
confidence: 99%
“…In a similar [7] advocated for the use of carbon fibre and glass fibre in prosthetic applications due to the low density, lightweight quality, and tremendous strength that these materials possess. The carbon-fiber laminated prosthetic foot has been shown to retain elastic energy in recent studies [8]. This not only aids in forward motion, but also reduces the impact felt by the remaining limbs [9].…”
Section: Introductionmentioning
confidence: 99%
“…Study on the static and dynamic activity of a carbon fiber nylon 12 composite hip resurfacing prosthesis was done in order to assess the prosthesis′ fatigue existence. The results showed that a hip resurfacing prosthesis made entirely of carbon fiber nylon 12 composite was resistant to fatigue failure [14]. In another study, a hip implant was manufactured using carbon fiber nylon 12 composite material through injection molding and its compressive strength investigated.…”
Section: Introductionmentioning
confidence: 99%